A Review of Practices and Technologies for Odor Control in Swine Production Facilities - Liu, Zifei; Powers, Wendy; Mukhtar, Saqib (My University, 2014)
The objective of this article is to provide a systematic review on practices and technologies for odor control in swine production facilities and to summarize available data on odor reduction effectiveness of promising technologies, as well as provide information on key parameters and associated costs. Odors from swine facilities comprise hundreds of chemicals, including volatile organic compounds (VOC), ammonia (NH₃), and hydrogen sulfide (H₂S). The medians of emission rates from swine houses in literature are 5 OU/s/pig for odor, and 0.4, 2.8, and 0.1 kg/yr/pig for VOC, NH₃, and H₂S respectively. The medians of emission rates from swine manure storage facilities in literature are 5 OU/s/m2 for odor, and 1.4, 2.1, and 0.2 kg/yr/pig for VOC, NH₃, and H₂S, respectively. Facility maintenance and management practices to reduce impact of odor are reviewed in regard to regular cleaning of facilities, ventilation, floor design, drainage and manure removal systems, frequent manure removal, manure storage, and odor separation distances. Approaches to control odor and air pollution can be classified into three categories: ration/diet modification, manure treatment, capture/treatment of emitted gases and enhanced dispersion. Each of these mitigation approaches includes several specific technologies, which are summarized in tables with an evaluation of overall cost and brief comments on advantages or limitations of each technology. Diet modification strategies have been shown to reduce NH₃ emissions effectively with low cost and should be considered as a best management practices, although their effectiveness in reducing odor is still uncertain. Permeable covers and biofilters seem to have great potential to be the most promising and cost effective technologies for manure storage facilities and swine houses respectively. However, both of the technologies need careful maintenance to perform effectively. Care must be taken to select technologies that are compatible with the management capabilities of the operation to prevent potential failure due to mismanagement.
Keywords: Ammonia; Biofilter; Cover; Diet; Manure; Emission; Hydrogen sulfide; Mitigation; Odor